The Importance of Background Knowledge in Covid-related Internet Memes - Cighir, Anca Irina (International Journal of Language and Literary Studies, 2024)
2020 was the most challenging year of our lives so far: Covid-19 was our enemy; it was everywhere, on each and every continent, except Antarctica. We were living in a dystopian world and could not see any way out. Besides isolating ourselves and wearing masks everywhere, we had no means to protect ourselves and our loved ones. The only way to stay in touch with our peers and loved ones were our phones and the internet. The internet connected us to people all over the world, we were not alone, we shared feelings and we shared memes. Internet memes were the easiest genre of communication as they expressed so much in such a short time: with only two clicks (copy and paste) we were able to share it with all the people we wanted to. Our research focuses on the analysis of conceptual metaphors found in Internet memes during the Covid-19 pandemic in order to better understand what kept a lot of the people sane during those days.